Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1108/dta-10-2020-0253
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of pollution Citizen Science projects from the perspective of Data Science and Open Science

Abstract: PurposeCitizen Science – public participation in scientific projects – is becoming a global practice engaging volunteer participants, often non-scientists, with scientific research. Citizen Science is facing major challenges, such as quality and consistency, to reap open the full potential of its outputs and outcomes, including data, software and results. In this context, the principles put forth by Data Science and Open Science domains are essential for alleviating these challenges, which have been addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In 2016, a set of guiding principles were instantiated with the aim to establish a standard for scientific data, ensuring that it is FAIR: Findable, Accessible, Interoperable and Reusable (Wilkinson et al., 2016). Nevertheless, it has been shown that despite the development of tools to facilitate open science, abounding toolkits and data and code repositories, the potential of citizen science to be practiced as open science is not always realised by those responsible for the projects, with missing information in published outcomes having a significant impact on the openness of the research projects that were analysed (Suter et al., 2023) and low uptake of complex data management plan tools (Roman et al., 2021). However, CS projects such as StreetSpectra provide an exemplary testbed for the usability of open science infrastructure and for testing how FAIR research is.…”
Section: Science Innovation Through Citizen Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, a set of guiding principles were instantiated with the aim to establish a standard for scientific data, ensuring that it is FAIR: Findable, Accessible, Interoperable and Reusable (Wilkinson et al., 2016). Nevertheless, it has been shown that despite the development of tools to facilitate open science, abounding toolkits and data and code repositories, the potential of citizen science to be practiced as open science is not always realised by those responsible for the projects, with missing information in published outcomes having a significant impact on the openness of the research projects that were analysed (Suter et al., 2023) and low uptake of complex data management plan tools (Roman et al., 2021). However, CS projects such as StreetSpectra provide an exemplary testbed for the usability of open science infrastructure and for testing how FAIR research is.…”
Section: Science Innovation Through Citizen Sciencementioning
confidence: 99%
“…Non-specialists and volunteers are less likely to "work through" obfuscated or confusing datasets and technological quirks and difficulties; they are an unforgiving audience for collaborative platforms. Working with non-specialist citizen scientists on open science allows for infrastructure to be developed that supports proper scientific method while streamlining processes, such as in the co-creation process of the ACTION DMP tool(Roman et al, 2021),…”
mentioning
confidence: 99%
“…Representation among different genders, backgrounds, nationalities, and career stages expands perspectives in a project (Sandbrook et al., 2019 ). Local non‐scientists can be great assets to projects, bringing valuable contextual information (Roman et al., 2021 ). The American Geophysical Union's Thriving Earth Exchange offers one opportunity for scientists to connect with communities seeking science support to resolve challenges that require the expertise of scientists, such as issues associated with municipal water quality and community forest health.…”
Section: Community Engagement Community Science Education and Stakeho...mentioning
confidence: 99%
“…Finally, for citizens to go beyond the provided solutions, they need to develop the capacity to use the data and create innovative solutions for their own needs. Based on this perspective, the last dimension focuses on capacity building [3,16,43,53], as shown in Figure 1.…”
Section: Design and Implementation Frameworkmentioning
confidence: 99%